Flexible RFID tag for bottle labelling - Rodrigues, David (2022)
This paper describes the design, manufacturing and range measurement of an UHF (ultra high frequency) RFID (radio frequency identification) tag to apply on a glass bottle filled with water. To achieve this, a free-space matched RFID antenna is studied and modifications are made in order reduce its size drastically and to turn it functional when applied to a bottle with water. Later, range measurement tests are made on the fabricated tag.